Asthma and overweight/obese: double trouble for urban children. (27th May 2016) - Wiesenthal, Elise N.; Fagnano, Maria; Cook, Stephen; Halterman, Jill S.
Abstract: Objective : To evaluate the effects of overweight/obese versus normal weight on symptoms, activity limitation and health care utilization among a group of urban children with persistent asthma. Methods : Data were obtained from the School Based Asthma Therapy trial. We enrolled 530 children ages 3–10 with persistent asthma from 2006 to 2009 (response rate: 74%). We conducted in-home interviews to assess symptoms and health care utilization. We measured height and weight in school nurse offices to determine BMI percentile, and compared normal weight children to overweight/obese (BMI >85th percentile) children. Bivariate and multivariate analyses were used. Results : We collected BMI data from 472 children (89%); 49% were overweight/obese. When controlling for child race, child ethnicity, intervention group, caregiver age and screen time, overweight/obese children had more days with asthma symptoms (4.25 versus 3.42/2 weeks, p = 0.035) and more activity limitation (3.43 versus 2.55/2 weeks, p = 0.013) compared to normal weight children. Overweight/obese children were more likely to have had an ED visit or hospitalization for any reason (47% versus 36%, OR 1.5, 95% CI 1.01, 2.19), and there was a trend for overweight/obese children to have more acute asthma visits in the past year (1.68 versus 1.31, p = 0.090). Overweight/obese children were not more likely to be taking a daily preventive inhaled corticosteroid (OR 1.0, 95% CI 0.68, 1.56). Conclusions : Overweight/obese children with persistent asthma experience more asthma symptoms, activity limitation and health care utilization compared to normal weight children, with no increased use of inhaled corticosteroids. Further efforts are needed to improve the health of these children.